Is there a correlation between humeral osteoarthritis and glenoid morphology according to Walch?. (7th June 2022) - Vetter, Philipp; Magosch, Petra; Habermeyer, Peter
Abstract : Aims: The aim of this study was to determine whether there is a correlation between the grade of humeral osteoarthritis (OA) and the severity of glenoid morphology according to Walch. We hypothesized that there would be a correlation. Methods: Overal, 143 shoulders in 135 patients (73 females, 62 males) undergoing shoulder arthroplasty surgery for primary glenohumeral OA were included consecutively. Mean age was 69.3 years (47 to 85). Humeral head (HH), osteophyte length (OL), and morphology (transverse decentering of the apex, transverse, or coronal asphericity) on radiographs were correlated to the glenoid morphology according to Walch (A1, A2, B1, B2, B3), glenoid retroversion, and humeral subluxation on CT images. Results: Increased humeral OL correlated with a higher grade of glenoid morphology (A1-A2-B1-B2-B3) according to Walch (r = 0.672; p < 0.0001). It also correlated with glenoid retroversion (r = 0.707; p < 0.0001), and posterior humeral subluxation ( r = 0.452; p < 0.0001). A higher humeral OL (odds ratio (OR) 1.17; 95% confidence interval (CI) 1.03 to 1.32; p = 0.013), posterior humeral subluxation (OR 1.11; 95% CI 1.01 to 1.22; p = 0.031), and glenoid retroversion (OR 1.48; 95% CI 1.30 to 1.68; p < 0.001) were independent factors for a higher glenoid morphology. More specifically, a humeral OL of ≥ 13 mm was indicative of eccentric glenoid types B2 and B3 (OR 14.20; 95% CI 5.96 to 33.85). Presence of an aspherical HH in the coronal plane was suggestive of glenoid types B2 and B3 (OR 3.34; 95% CI 1.67 to 6.68). Conclusion: The criteria of humeral OL and HH morphology are associated with increasing glenoid retroversion, posterior humeral subluxation, and eccentric glenoid wear. Therefore, humeral radiological parameters might hint at the morphology on the glenoid side. Cite this article: Bone Jt Open 2022;3(6):463–469.